Sistem Aplikasi untuk Penyaluran Bantuan Bahan Pangan Menggunakan Aplikasi PGC (Pos Giro Cash) - Mohammad Rachel (Journal of Engineering and Applied Technology, 2025)
PT Pos Indonesia (Persero) is a state-owned enterprise engaged in services, particularly communication and delivery services, as well as financial services through post offices. As a state-owned enterprise, PT Pos Indonesia is committed to maintaining public trust and providing optimal services to the government and the community. Post offices serve as a means for various transactions, such as sending letters and packages, paying bills, withdrawing money, and selling stamps. In supporting the distribution of social assistance, PT Pos Indonesia has developed the Pos Giro Cash application, which is used to document the homes of beneficiary families (KPM) of the Sembako Program. This application aims to minimize the risk of misdirected assistance by collecting and managing recipient data accurately. Social assistance is a form of government spending provided in the form of money, goods, or services to protect the community from social risks and improve welfare. One form of social assistance is food assistance, which aims to ensure that the community has access to sufficient and nutritious food. This application system was developed as a set of integrated elements to achieve the goal of targeted and effective assistance distribution.